Hormonal contraceptives and the risk of suicide: a systematic review and meta-analysis. (August 2020) - Pérez-López, Faustino R.; Pérez-Roncero, Gonzalo R.; López-Baena, María T.; Santabárbara, Javier; Chedraui, Peter
Highlights: Consumed suicides were meta-analyzed in three cohort studies. The use of combined hormonal contraceptives is associated to suicide risk. Attempted suicide is not reported among contraceptive users. Women at higher suicidal risk should be properly identified. Abstract: Objective: To assess the effect of hormonal contraceptive use over the risk of suicide. Method: Systematic review and meta-analysis of observational studies retrieved from five search engines until September 2019, comparing the use of any hormonal contraceptive versus non-hormonal contraceptive use or no use. Primary outcome was consumed suicide, and secondary outcomes were suicidal attempt and ideation. Random effects meta-analyses with the inverse variance method were used to evaluate the effects of exposure over outcomes. Effect was calculated as risk ratio (RR) with their corresponding 95% confidence interval (CI). Risk of bias was assessed with the Newcastle-Otawa Scale. Results: There were no randomized controlled trials concerning suicide and hormonal contraceptive use. Only three cohort studies ( n  = 184, 721 women), that evaluated the primary outcome (consumed suicide), were included in the meta-analysis. Hormonal contraceptive use was associated to a higher risk of consumed suicide (RR = 1.36, 95% CI 1.06 to 1.75, P  =  0.015, I 2  = 0%). There were no secondary outcomes in at least two cohorts. Conclusion: This meta-analysis found a positive association between hormonal contraceptive use and consumed suicides. Prior to their use, populations at suicidal risk should be properly evaluated.